Weave-pattern-dependent fabric piezoelectric pressure sensors based on polyvinylidene fluoride nanofibers electrospun with 50 nozzles - Da Bin Kim; Ju Han; Sun Min Sung; Min Seong Kim; Bo Kyoung Choi; Sung Jun Park; Hyae Rim Hong; Hong Je Choi; Byeong Kon Kim; Chung Hee Park; Jong Hoo Paik; Joon-Seok Lee; et al. (npj Flexible Electronics, 2022)
Abstract Wearable pressure sensors having versatile device structures have been extensively investigated to achieve high sensitivity under mechanical stimuli. Here, we introduce piezoelectric pressure sensors based on fabrics woven using polyvinylidene fluoride (PVDF) weft and polyethylene terephthalate (PET) warp yarns with different weave structures: 1/1 (plain), 2/2, and 3/3 weft rib patterns. The dependence of the pressure-sensing performance on the weave pattern is demonstrated with an actual large-scale fabric up to the ~2 m scale. An optimized pressure sensor with a 2/2 weft rib pattern produced a high sensitivity of 83 mV N−1, which was 245% higher than that of the 1/1 pattern. The detection performance of the optimal fabric was extensively evaluated with a variety of ambient input sources, such as pressing, bending, twisting, and crumpling, as well as various human motions. Further, a large all-fabric pressure sensor with arrayed touch pixel units demonstrated highly sensitive and stable sensing performance.